2022
DOI: 10.1186/s12963-022-00293-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing two data collection methods to track vital events in maternal and child health via community health workers in rural Nepal

Abstract: Background Timely tracking of health outcomes is difficult in low- and middle-income countries without comprehensive vital registration systems. Community health workers (CHWs) are increasingly collecting vital events data while delivering routine care in low-resource settings. It is necessary, however, to assess whether routine programmatic data collected by CHWs are sufficiently reliable for timely monitoring and evaluation of health interventions. To study this, we assessed the consistency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Of note, to investigate this limitation further, we conducted a comparison of birth history data with programmatic data on births. We found that although more were identified in programmatic data, reporting on birth location was largely consistent among births identified by both methods [25].…”
Section: Limitationsmentioning
confidence: 70%
See 1 more Smart Citation
“…Of note, to investigate this limitation further, we conducted a comparison of birth history data with programmatic data on births. We found that although more were identified in programmatic data, reporting on birth location was largely consistent among births identified by both methods [25].…”
Section: Limitationsmentioning
confidence: 70%
“…The target study population consisted of married women of reproductive age (15-49 years) in Achham and Dolakha. We used a census methodology to recruit all eligible participants from our study catchment areas [25]. Women who provided consent to enroll and receive antenatal and postnatal care and to use their data in the study were included in data analysis.…”
Section: Study Populationmentioning
confidence: 99%